Green technologies for development: transfer, trade and cooperation - Herbert-Copley, Brent (IDRC OttawaCA, 1993)
Looks at the role of technology in combatting environmental degradation and the potential of international cooperation in fostering this role. Recognizes the linkages between poverty, population and sustainable development.